When Our Space Closes, It Opens Our Minds - Ambrus Tünde (Acta Universitatis Sapientiae: European and Regional Studies, 2020)
The object of the study is the problem of the ongoing epidemic, which affects the entire society and many fields of activity. Using associative logic, I focused on the approach which states that development based on ecology cannot be learned at school as the key of development is awareness. I presented the topic examining the social factors in three time period sections (Reorganization 1.0, 2.0, and 3.0), and I analysed it using historical sources as well as my previous studies referring to village research.